2018
DOI: 10.21767/2348-1927.1000116
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Gut Microbiome in Brain Chemistry and Behavior

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Short-chain fatty acids (SCFAs), such as acetic, propionic, and butyric acids, are major products of the bacterial fermentation of nondigestible dietary fiber in the gastrointestinal tract 47 that are able to regulate the homeostasis of microglia and macrophages of the CNS. 15 Other studies showed that butyrate-producing bacteria potentially reduced anxiety in rats and lowered psychological stress in humans. 48 The butyrate producers Clostridium XIVa, Oscillibacter, and Coprococcus 49 were all increased in the krill oil-treated groups but decreased in the donepezil-treated group compared with the model group.…”
Section: ■ Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Short-chain fatty acids (SCFAs), such as acetic, propionic, and butyric acids, are major products of the bacterial fermentation of nondigestible dietary fiber in the gastrointestinal tract 47 that are able to regulate the homeostasis of microglia and macrophages of the CNS. 15 Other studies showed that butyrate-producing bacteria potentially reduced anxiety in rats and lowered psychological stress in humans. 48 The butyrate producers Clostridium XIVa, Oscillibacter, and Coprococcus 49 were all increased in the krill oil-treated groups but decreased in the donepezil-treated group compared with the model group.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Short-chain fatty acids (SCFAs), such as acetic, propionic, and butyric acids, are major products of the bacterial fermentation of nondigestible dietary fiber in the gastrointestinal tract that are able to regulate the homeostasis of microglia and macrophages of the CNS . Other studies showed that butyrate-producing bacteria potentially reduced anxiety in rats and lowered psychological stress in humans .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations